2013
DOI: 10.1126/scisignal.2003906
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of the Conserved AAA+ ATPases Pontin and Reptin on the Signaling Landscape Meeting Information: The First International Workshop on Pontin (RUVBL1) and Reptin (RUVBL2) took place at the European Institute for Chemistry and Biology in Pessac, France, 16 to 19 October 2012.

Abstract: Pontin (also known as RUVBL1 and RVB1) and Reptin (also called RUVBL2 and RVB2) are related members of the large AAA+ (adenosine triphosphatase associated with diverse cellular activities) superfamily of conserved proteins. Various cellular functions depend on Pontin and Reptin, mostly because of their functions in the assembly of protein complexes that play a role in the regulation of cellular energetic metabolism, transcription, chromatin remodeling, and the DNA damage response. Little is known, though, abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Electrophoretic mobility gel shift assays showed that Reptin or Pontin monomers form complexes with nucleosome-DNA substrates (Fig. 1, C and D, lanes [1][2][3][4] in the same range of protein concentrations needed for binding to naked DNA (Fig. 1, C and D, lanes [13][14][15][16].…”
Section: Reptin and Pontin Bind To Nucleosomes As An Active Complex-mentioning
confidence: 96%
“…Electrophoretic mobility gel shift assays showed that Reptin or Pontin monomers form complexes with nucleosome-DNA substrates (Fig. 1, C and D, lanes [1][2][3][4] in the same range of protein concentrations needed for binding to naked DNA (Fig. 1, C and D, lanes [13][14][15][16].…”
Section: Reptin and Pontin Bind To Nucleosomes As An Active Complex-mentioning
confidence: 96%
“…Recent studies have shown that, aside from the R2TP complex, RUVBL1/2 are also parts of other functionally relevant complexes, such as chromatin remodeling complexes TIP60, SWR/SRCAP, and INO80 and the Fanconi anemia core complex that controls DNA interstrand cross-link repair and function, and regulate telomerase biogenesis and mitosis (19,(43)(44)(45). Given the PIH1D1-independent interaction of ECD with RUVBL1, the potential roles of ECD via these alternative complexes will be of great future interest.…”
Section: Discussionmentioning
confidence: 99%
“…These AAAϩ ATPases are implicated in several cellular processes as part of large macromolecular assemblies, such as INO80, SWR1, TIP60, and R2TP complexes, among others (20,21). Despite both proteins being essential, not much is known about their mechanism of action, and the functional significance of the several oligomeric forms of RuvBL1 and RuvBL2 is still unclear (20,21). We tested the interaction of YY1 with the RuvBL1 and RuvBL2 ATPases, showing that this interaction takes place also with purified YY1 oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…RuvB assembles as hexameric rings, and its DNA-dependent ATPase activity provides the energy for branch migration (22). RuvBL1 and RuvBL2 are essential in multiple processes including transcription, DNA repair, and nonsense-mediated mRNA decay, and their overexpression is associated with tumorigenesis (20,21).…”
Section: Yin Yang 1 (Yy1)mentioning
confidence: 99%
See 1 more Smart Citation